Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Certainly! Let's solve the expression:
[tex]\[ E = \sqrt{5 + 2 \sqrt{6}} \cdot \sqrt{5 - 2 \sqrt{6}} \][/tex]
First, let's define two terms for simplicity:
[tex]\[ a = \sqrt{5 + 2 \sqrt{6}} \][/tex]
[tex]\[ b = \sqrt{5 - 2 \sqrt{6}} \][/tex]
We need to find the product [tex]\( E = a \cdot b \)[/tex].
To find this, we will consider the product of the expressions under the square roots:
[tex]\[ E^2 = (\sqrt{5 + 2 \sqrt{6}} \cdot \sqrt{5 - 2 \sqrt{6}})^2 \][/tex]
When the square roots are multiplied and squared, we get:
[tex]\[ E^2 = (5 + 2 \sqrt{6})(5 - 2 \sqrt{6}) \][/tex]
Recall the algebraic identity for the difference of squares:
[tex]\[ (x + y)(x - y) = x^2 - y^2 \][/tex]
Here, [tex]\( x = 5 \)[/tex] and [tex]\( y = 2 \sqrt{6} \)[/tex]. Applying this identity:
[tex]\[ E^2 = 5^2 - (2 \sqrt{6})^2 \][/tex]
Calculate each square separately:
[tex]\[ 5^2 = 25 \][/tex]
[tex]\[ (2 \sqrt{6})^2 = 4 \cdot 6 = 24 \][/tex]
So we have:
[tex]\[ E^2 = 25 - 24 = 1 \][/tex]
Taking the square root of both sides, we find:
[tex]\[ E = \sqrt{1} = 1 \][/tex]
Thus, the result of the original expression is:
[tex]\[ E = 1 \][/tex]
Upon verification with numerical calculations:
- We have [tex]\( \sqrt{5 + 2 \sqrt{6}} \approx 3.146264369941972 \)[/tex]
- and [tex]\( \sqrt{5 - 2 \sqrt{6}} \approx 0.31783724519578294 \)[/tex].
Their product is:
[tex]\[ 3.146264369941972 \times 0.31783724519578294 \approx 1.000000000000002 \][/tex]
Considering the small numerical tolerance or rounding errors, we can confidently conclude:
[tex]\[ E = 1 \][/tex]
[tex]\[ E = \sqrt{5 + 2 \sqrt{6}} \cdot \sqrt{5 - 2 \sqrt{6}} \][/tex]
First, let's define two terms for simplicity:
[tex]\[ a = \sqrt{5 + 2 \sqrt{6}} \][/tex]
[tex]\[ b = \sqrt{5 - 2 \sqrt{6}} \][/tex]
We need to find the product [tex]\( E = a \cdot b \)[/tex].
To find this, we will consider the product of the expressions under the square roots:
[tex]\[ E^2 = (\sqrt{5 + 2 \sqrt{6}} \cdot \sqrt{5 - 2 \sqrt{6}})^2 \][/tex]
When the square roots are multiplied and squared, we get:
[tex]\[ E^2 = (5 + 2 \sqrt{6})(5 - 2 \sqrt{6}) \][/tex]
Recall the algebraic identity for the difference of squares:
[tex]\[ (x + y)(x - y) = x^2 - y^2 \][/tex]
Here, [tex]\( x = 5 \)[/tex] and [tex]\( y = 2 \sqrt{6} \)[/tex]. Applying this identity:
[tex]\[ E^2 = 5^2 - (2 \sqrt{6})^2 \][/tex]
Calculate each square separately:
[tex]\[ 5^2 = 25 \][/tex]
[tex]\[ (2 \sqrt{6})^2 = 4 \cdot 6 = 24 \][/tex]
So we have:
[tex]\[ E^2 = 25 - 24 = 1 \][/tex]
Taking the square root of both sides, we find:
[tex]\[ E = \sqrt{1} = 1 \][/tex]
Thus, the result of the original expression is:
[tex]\[ E = 1 \][/tex]
Upon verification with numerical calculations:
- We have [tex]\( \sqrt{5 + 2 \sqrt{6}} \approx 3.146264369941972 \)[/tex]
- and [tex]\( \sqrt{5 - 2 \sqrt{6}} \approx 0.31783724519578294 \)[/tex].
Their product is:
[tex]\[ 3.146264369941972 \times 0.31783724519578294 \approx 1.000000000000002 \][/tex]
Considering the small numerical tolerance or rounding errors, we can confidently conclude:
[tex]\[ E = 1 \][/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.